2020
DOI: 10.3390/nu12082436
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Cardiovascular Disease Risk Among Individuals with Familial Hypercholesterolemia: Systematic Review and Meta-Analysis

Abstract: Background: Although a cholesterol-lowering diet and the addition of plant sterols and stanols are suggested for the lipid management of children and adults with familial hypercholesterolemia, there is limited evidence evaluating such interventions in this population. Objectives: To investigate the impact of cholesterol-lowering diet and other dietary interventions on the incidence or mortality of cardiovascular disease and lipid profile of patients with familial hypercholesterolemia. Search methods: Relevant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 55 publications
(204 reference statements)
0
39
0
Order By: Relevance
“…Notably, our work also highlighted that, in adequate study settings, diet appears to impact LDL-C and other plasma lipids similarly among individuals with HeFH than among non-FH individuals – a finding that corroborates observational data on the relationship between dietary intakes and plasma lipids in HeFH [ 5 , 39 , 40 ]. Indeed, six of the seven interventions on phytosterol (sterols and/or stanols) supplementation we reviewed reported significant reductions in LDL-C among individuals with HeFH, ranging from 5 to 15% [ 7 ]. These reductions are consistent with mean effects on LDL-C reported in meta-analyses on phytosterol supplementation interventions conducted among non-FH individuals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, our work also highlighted that, in adequate study settings, diet appears to impact LDL-C and other plasma lipids similarly among individuals with HeFH than among non-FH individuals – a finding that corroborates observational data on the relationship between dietary intakes and plasma lipids in HeFH [ 5 , 39 , 40 ]. Indeed, six of the seven interventions on phytosterol (sterols and/or stanols) supplementation we reviewed reported significant reductions in LDL-C among individuals with HeFH, ranging from 5 to 15% [ 7 ]. These reductions are consistent with mean effects on LDL-C reported in meta-analyses on phytosterol supplementation interventions conducted among non-FH individuals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the genetic nature of this disease, diet has traditionally been considered as a secondary therapy, with limited effectiveness relative to medication [ 1 , 5 ]. Even though the literature on diet in HeFH management remains limited, previous systematic reviews and meta-analyses of dietary interventions among individuals with HeFH suggested that no conclusions can be made about the effectiveness of diet in HeFH [ 6 , 7 ]. Still, none of the previous reviews thoroughly assessed the impact on plasma lipids of dietary interventions conducted in HeFH, in line with the intervention design per se [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is even possible that in the past the combination of high cholesterol and relative lack of food benefitted those who got bacterial infections and improved their survival. In modern times, however, the situation is quite the opposite, as a large proportion of undiagnosed HeFH patients (as subjects in the general population) are likely to follow an unhealthy lifestyle, which induces several proatherogenic changes in lipoproteins thereby further increasing their risk for developing premature ASCVD [ 13 ].…”
Section: Infection As a Proatherogenic Factormentioning
confidence: 99%